You are on page 1of 3

Electricity and Magnetism II - Homework Assignment 5

Alejandro G´omez Espinosa

March 5, 2013
Jackson, 9.6 (a) Starting from the general expression (9.2) for A and the corresponding expression for
Φ, expand both R = |x−x

| and t

= t −R/c to first order in |x

|/r to obtain the electric dipole
potentials for arbitrary time variation
Φ(x, t) =
1
4πε
0
_
1
r
2
n · p
ret
+
1
cr
n ·
∂p
ret
∂t
_
(1)
A(x, t) =
µ
0
4πr
∂p
ret
∂t
(2)
where p
ret
= p(t

= t −r/c) is the dipole moment evaluated at the retarded time measured from
the origin.
Equation (9.2) is the vector potential A(x, t) in the Lorenz gauge:
A(x, t) =
µ
0

_
d
3
x

_
dt

J(x

, t

)
|x −x

|
δ
_
t

+
|x −x

|
c
−t
_
(3)
Let us use the approximation |x−x

| ≈ r −n· x

, as suggested in (9.7) to calculate the time t

:
t

= t −
|x −x

|
c
≈ t −
r
c
+
n · x

c
(4)
Also, let us approximate the factor:
1
|x −x

|
=
1
r −n · x


1
r
+
n · x

r
2
(5)
Plugging (4) and (5) into (3), we obtain:
A(x, t) =
µ
0

_
d
3
x

_
dt

J(x

, t

)
|x −x

|
δ
_
t

+
|x −x

|
c
−t
_
=
µ
0

_
d
3
x

J
_
x

, t −
|x−x

|
c
_
|x −x

|

µ
0

_
d
3
x

_
1
r
+
n · x

r
2
_
J
_
x

, t −
r
c
_

µ
0

_
d
3
x

_
1
r
_
J
ret
= −
µ
0
4πr
_
d
3
x

x

(∇

· J
ret
)
=
µ
0
4πr
_
d
3
x

x

∂ρ
ret
∂t
=
µ
0
4πr

∂t
_
d
3
x

x

ρ
ret
=
µ
0
4πr
∂p
ret
∂t

gomez@physics.rutgers.edu
1
In the case of the scalar potential, the corresponding expression is given by:
Φ(x, t) =
1
4πε
0
_
d
3
x

_
dt

ρ(x

, t

)
|x −x

|
δ
_
t

+
|x −x

|
c
−t
_
(6)
Here, the charge density can be expand using (4):
ρ(x

, t

) = ρ
_
x

, t −
r
c
_
+
n · x

c

∂t
ρ
_
x

, t −
r
c
_
= ρ
ret
+
n · x

c
∂ρ
ret
∂t
(7)
Following the same procedure as before, and plugging (7) into (6), we found:
Φ(x, t) =
1
4πε
0
_
d
3
x

_
dt

ρ(x

, t

)
|x −x

|
δ
_
t

+
|x −x

|
c
−t
_

1
4πε
0
_
d
3
x

_
1
r
+
n · x

r
2
_
ρ
_
x

, t −
r
c
_
=
1
4πε
0
_
d
3
x

_
1
r
+
n · x

r
2
__
ρ
ret
+
n · x

c
∂ρ
ret
∂t
_
=
1
4πε
0
_
d
3
x

_
ρ
ret
r
+
n · x

r
2
ρ
ret
+
n · x

cr
∂ρ
ret
∂t
+
(n · x

)
2
cr
2
∂ρ
ret
∂t
_

1
4πε
0
_
d
3
x

_
ρ
ret
r
+
n · x

r
2
ρ
ret
+
n · x

cr
∂ρ
ret
∂t
_
=
1
4πε
0
_
Q +
n · p
ret
r
2
+

cr
∂p
ret
∂t
_
that is the same as (1) plus the total charge distribution.
(b) Calculate the dipole electric and magnetic fields directly from these potentials and show that
B(x, t) =
µ
0

_

1
cr
2
n ×
∂p
ret
∂t

1
c
2
r
n ×

2
p
ret
∂t
2
_
(8)
E(x, t) =
1
4πε
0
__
1 +
r
c

∂t
__
3n(n · p
ret
) −p
ret
r
3
_
+
1
c
2
r
n ×
_
n ×

2
p
ret
∂t
2
__
(9)
Let us compute the magnetic field:
B = ∇×A
= ∇×
_
µ
0
4πr
∂p
ret
∂t
_
=
µ
0

n ×
_

_
1
r
_
∂p
ret
∂t
+
1
r

_
∂p
ret
∂t
__
=
µ
0

n ×
_

1
r
2
∂p
ret
∂t
+
1
r

2
p
ret
∂t∂r
_
=
µ
0

n ×
_

1
r
2
∂p
ret
∂t

1
rc

2
p
ret
∂t
2
_
where the last step comes from the dependency of the dipole moment:
p
ret
= p
_
t −
r
c
_

∂p
∂r
= −
1
c
∂p
∂t
2
In the case of the electric field:
E = −∇Φ −
∂A
∂t
= −∇
_
1
4πε
0
_
n · p
ret
r
2
+

cr
∂p
ret
∂t
__


∂t
_
µ
0
4πr
∂p
ret
∂t
_
= −
1
4πε
0
_

_
n · p
ret
r
2
_
+∇
_

cr
∂p
ret
∂t
__

µ
0
4πr

2
p
ret
∂t
2
= −
1
4πε
0
_

_
r · p
ret
r
3
_
+∇
_

cr
2
∂p
ret
∂t
__

µ
0
4πr

2
p
ret
∂t
2
= −
1
4πε
0
_
p
ret
r
3

3r(r · pret)
r
5

r
cr
4
_
r ·
∂p
ret
∂t
_
+
1
cr
2
∂p
ret
∂t

2r
cr
4
_
r ·
∂p
ret
∂t
_

r
c
2
r
3
_
r ·

2
p
ret
∂t
2
__

1
4πε
0
c
2
r

2
p
ret
∂t
2
= −
1
4πε
0
_
1
r
3
(p
ret
−3n(n · p
ret
)) +
1
cr
2

∂t
(p
ret
−3n(n · p
ret
))
+
1
c
2
r

2
∂t
2
(p
ret
−n(n · p
ret
))
_
=
1
4πε
0
__
1 +
r
c

∂t
__
3n(n · p
ret
) −p
ret
r
3
_
+
1
c
2
r
n ×
_
n ×

2
p
ret
∂t
2
__
(c) Show explicitly how you can go back and forth between these results and the harmonic fields of
(9.18) by the substitutions −iω ↔∂/∂t and pe
ikr−iωt
↔p
ret
(t

).
Making this substitutions into (8) and (9), we found:
B =
µ
0

_

1
cr
2
n ×
∂p
ret
∂t

1
c
2
r
n

2
p
ret
∂t
2
_
=
µ
0

n ×
_

1
cr
2
(−iω)pe
ikr−iωt

1
c
2
r
_
−ω
2
_
pe
ikr−iωt
_
=
µ
0

(n ×p)
_

cr
2
+
ω
2
c
2
r
_
e
ikr−iωt
=
µ
0
ω
4πcr
(n ×p)
_
i
r
+
ω
c
_
e
ikr−iωt
E(x, t) =
1
4πε
0
__
1 +
r
c

∂t
__
3n(n · p
ret
) −p
ret
r
3
_
+
1
c
2
r
n ×
_
n ×

2
p
ret
∂t
2
__
=
1
4πε
0
_
_
1 +
r
c
(−iω)
_
_
3n(n · pe
ikr−iωt
) −pe
ikr−iωt
r
3
_
+
1
c
2
r
n ×
_
n ×(−ω
2
)pe
ikr−iωt
_
_
=
1
4πε
0
__
1 −
irω
c
__
3n(n · p) −p
r
3
_

ω
2
c
2
r
n ×(n ×p)
_
e
ikr−iωt
3